Kesiapan Fasilitas Pelayanan Kesehatan Indonesia Dalam Perdagangan Bebas Masyarakat Ekonomi ASEAN - Mugi Wahidin; Syarifah Nuraini; Ady Iswadhy Thomas (Buletin Penelitian Sistem Kesehatan, 2019)
The ASEAN Economic Community (MEA) is a form of ASEAN economic integration, including the free trade of goods and services in health sector, which one of them is health services facilities. The study aimed to determine the readiness of health service facilities in Indonesia in dealing with free trade in health goods and services within the framework of the ASEAN Economic Community (MEA). This was qualitative study with descriptive analysis. The data used was secondary data from the Ministry of Health, health professionals, health-related associations, research reports and other data sources. The steps of the study were data searches, in-depth interviews and Focus Group Discussion with related parties. The facilities were specialist hospitals, specialistic clinics (medical specialist, dentistry specialist, medical and ambulatory evacuation clinics, specialist nursing clinics), acupuncture service facilities and primary clinics. Readiness was justifi ed by the availability of the health services facilities and supported regulation. The results of the study indicated that health service facilities in Indonesia are quite ready to face the free trade in health-related goods and services, except residential health facility. This study recommended the preparation of related regulation, fulfi llment of health service equipments, providing data of spscialistic clinic, collaboration with Capital investment coordination board (BKPM), promortion and advocacy of foreign investment, acreditation for all health services fasilites, and monitoring and evaluation for health services. Abstrak Masyarakat Ekonomi ASEAN (MEA) merupakan sebuah bentuk integrasi ekonomi ASEAN, termasuk dalam halperdagangan bebas barang jasa di bidang kesehatan, dan salah satunya adalah fasilitas pelayanan kesehatan. Kajian bertujuan untuk mengetahui kesiapan fasilitas pelayanan kesehatan di Indonesia dalam menghadapi perdagangan bebas barang dan jasa kesehatan dalam kerangka Masyarakat Ekonomi ASEAN (MEA). Kajian ini adalah kajian kualitatif dengan analisis deskriptif. Data yang dikumpulkan adalah data sekunder yang bersumber dari Kementerian Kesehatan, profesi, asosiasi yang berkaitan, hasil penelitian maupun sumber data lainnya. Langkah kegiatan adalah melakukan penelusuran data, wawancara mendalam dan focus group discussion (FGD) dengan pihak yang berkaitan. Fasilitas pelayanan kesehatan meliputi rumah sakit spesialistik, klinik utama (kedokteran spesialis, kedokteran gigi spesialis, klinik evakuasi medik dan ambulatory, klinik keperawatan spesialis), fasilitas pelayanan akupunktur dan klinik pratama. Kesiapan dilihat dari ketersediaan fasyankes dan peraturan yang mendukung. Hasil kajian menunjukkan bahwa fasilitas pelayanan kesehatan Indonesia cukup siap dalam menghadapi perdagangan bebas barang dan jasa kesehatan, kecuali fasilitas kesehatan jasa pemukiman. Saran yang diberikan adalah penyiapan regulasi terkait, pemenuhan sarana danprasarana, pendataan klinik utama, kerja sama dengan Badan Koordinasi Penanaman Modal, sosialisasi dan advokasi tentang investasi asing, akreditasi seluruh fasyankes, dan monitoring dan evaluasi pelayanan kesehatan